The effectiveness of bioretention structures for metal retention and toxicity reduction of copper roof runoff - LaBarre, William J. (My University, 2015)
Concern has increased over the concentrations of copper in stormwater runoff from copper roofs due to its effects on sensitive aquatic biota. Stormwater control measures (SCMs) are being used as a way to treat effluent from various nonpoint pollution sources such as roadways and parking lots, but their efficacy has not been well demonstrated in the treatment of more concentrated sources such as copper roofs. Influent and effluent stormwater from a copper roof with two kinds of SCMs (bioretention planter boxes and biofiltration swales) were examined over a two year period to determine their ability to sequester copper and attenuate toxicity. The planter boxes averaged 93% copper removal and the swales averaged 97% removal. Effluent water toxicity was substantially decreased through water chemistry changes that reduce the bioavailability of copper as determined by the biotic ligand model and toxicity testing.
Introduction to the problem -- Attenuation of copper in runoff from copper roofing materials by two stormwater control measures -- Stormwater control measures decrease the toxicity of copper roof runoff.
(M.S.) -- Towson University, 2014.